Perancangan Aplikasi Daftar Menu dengan Implementasi Augmented Reality - Muhammad Alif Pandu Raharjo; Devi Afriyantari Puspa Putri (Jurnal Media Computer Science, 2026)
Digital technology has spread rapidly in the last several years. This growth has resulted in significant changes in various areas. The culinary sector stands out as one clear example. Studies indicate that innovation now plays a central role. It boosts how operations run more smoothly. At the same time, it improves what customers go through overall. Evidence points to the creation and rollout of a mobile app for menus. This app weaves in Augmented Reality, or AR, right into its core. Developers stuck to the waterfall approach for the whole process. They began with analyzing needs. Then came the in-depth planning of the system. After that, building it out, checking everything, and setting up ongoing support. AR comes into play by showing food options as lively 3D models. Users get to see dishes in a lifelike way. They can do this before deciding to order anything. Beyond that, the app offers extra tools to make things easier. Think quick searches through the menu. Or grouping items by type. There's also a spot to save favorites. Pop-ups give more details on selections. A basic cart handles picks. Checkout happens automatically through WhatsApp. For testing, the team used Black Box methods. This checked if functions worked as planned. To gauge how users felt, they applied the System Usability Scale, known as SUS. Results came back strong. Every part operated without issues. The SUS score topped 80. That points to strong approval from those who tried it. In the end, the app delivers a lively way to visualize and interact. It seems likely to help with marketing and sales. Small food businesses, like those in the MSME category, could find it especially handy.